AESTHETICS AND CULTURAL CHARACTERISTICS OF CHINESE TRADITIONAL PAINTING - SHĀNSHUǏ-HUÀ (山水画) - Ernesto Carlos Pujazon Patron; Jose Domingo Elias (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
Along with its multiple levels of importance, characterising a Chinese traditional painting in terms of its aesthetic arrangement-composition and visual meaning may be a challenging undertaking; yet, it also presents evolving features and constantly expanded connotations. A ’landscape painting’ is cultural (cultivated) rather than natural (innate); it is a cultural interpretation that renews the physical environmental reality. In the visual arts, ’landscape’ representation has acted as an emblem, playing a key role in the construction of China’s and Europe’s identities. Landscape ink-painting on Chinese paper or silk has a long history in China, stretching back over a thousand years, in contrast to Europe, where it evolved and developed considerably later. What is vital in this study is to determine how Chinese ink-painting has remained traditional in comparison to the evolution of western arts. Every civilization has its own aesthetic limits and standards for evaluating the manifestation of beauty through its arts, which impact its pursuit and creation. Chinese philosophers have a fundamentally conceptual understanding of nature that supports their belief in the cosmos’ order and harmony. Shānshuǐ-huà (山水画), akin to knowledge of the Western ’landscape,’ has been a continuous practise and vital feature of Chinese culture since the Song dynasty (960AD-1290AD), one of China’s finest creative epochs. This ink-painting tradition is linked to calligraphy methods known as painted poetry. As a result, in Chinese traditional painting, empty space is balanced against the painted area, the artwork keeps the beauty and balance the results; in Western art, figure-ground plays a visual equilibrium. This study analyses fundamental visual knowledge that embraces holistic aesthetic judgement for none-Chinese audiences; the concerns covered provide a flexible way for leading audiences in evaluating many aspects of Chinese ink-painting using their own understanding and imagination.